Luigi Moretti sebagai Pionir Arsitektur Parametrik - Junaedi, Multazam Akbar; Susanto, Angeline; Akbar, Fikri Sulaiman Kurnia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Luigi Moretti, The Pioneer of Parametric Architecture Parametric Architecture is a movement with new values that has evolved into a stylistic architectural choice. According to several experts, parametric architecture is a design method that uses generative computation with parameters as controls. Luigi Walter Moretti was the first Italian architect to conceptualize Parametric Architecture. This paper aims to provide new insights into Luigi Moretti's thoughts, which form the foundation and initial means for developing parametric architecture. Moretti's parametric thinking can be examined through a literature review of his published ideas. One of Moretti's significant contributions to Parametric Architecture is his article published in Moebius, which outlines eight formulas for defining Parametric Architecture. Additionally, it can be studied through case studies of key architectural works by Moretti, including Casa Il Girasole in Rome, Stadio Secondo le Curve di Equiappettibillita Visiva, and the Watergate Complex. These key works illustrate how Moretti used parametric as a design method, involving multiple parameters as design controls. By studying Luigi Moretti's ideas and his parameter-based design method, this paper aims to provide new insights into the origins of Parametric Architecture's development.